Parallel Mediation Analysis of Self-Efficacy and Career Aspiration in the Relationship between Achievement Motivation and Employability - Adi Kurniawan; Nurul Kamilia (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study examines the relationship between achievement motivation and employability, with self-efficacy and career aspiration as mediators, among final-year students in the Faculty of Economics and Business, Universitas Negeri Semarang. The research explores how psychological mechanisms connect motivation and employability within the university context. A quantitative method was applied using data from 315 students, analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The model showed strong reliability and validity, with factor loadings above 0.70 and composite reliability exceeding 0.90. The findings indicate that achievement motivation significantly affects self-efficacy, career aspiration, and employability. Both self-efficacy and career aspiration have significant effects on employability and mediate the relationship between motivation and employability, with career aspiration showing a stronger contribution. The results highlight how internal motivation and future orientation shape employable behavior and readiness for professional demands, providing theoretical and practical insights for higher education in enhancing students’ motivation and career development.